2023
DOI: 10.3389/fendo.2023.1106706
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing treatment for diabetic macular edema during cataract surgery

Abstract: Diabetic macular edema (DME) causes visual impairment in diabetic retinopathy (DR). Diabetes mellitus is a global epidemic and diabetic individuals are at risk of developing DR. Approximately 1 in 10 diabetic patients suffers from DME, which is the commonest cause of vision-threatening DR at primary-care screening. Furthermore, diabetes predisposes to a higher frequency and a younger onset of cataract, which further threatens vision in DME patients. Although cataract extraction is an effective cure, vision may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…The association between cataract surgery and progression of diabetic retinopathy has been highlighted by many authors [57,62]. Some authors have reported an increase in the risk of progression after cataract surgery, whereas others concluded no Cataract Surgery Complications: Vitreo-Retina Perspectives DOI: http://dx.doi.org/10.5772/intechopen.1001596 significant difference and the progression of diabetic retinopathy (DR) is part of the natural course of the disease [63][64][65].…”
Section: Progression Of Diabetic Retinopathy After Cataract Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…The association between cataract surgery and progression of diabetic retinopathy has been highlighted by many authors [57,62]. Some authors have reported an increase in the risk of progression after cataract surgery, whereas others concluded no Cataract Surgery Complications: Vitreo-Retina Perspectives DOI: http://dx.doi.org/10.5772/intechopen.1001596 significant difference and the progression of diabetic retinopathy (DR) is part of the natural course of the disease [63][64][65].…”
Section: Progression Of Diabetic Retinopathy After Cataract Surgerymentioning
confidence: 99%
“…Thereafter to address the need for any treatment of DR and/or DME prior to cataract surgery. Optimal management of DR and/or DME prior to cataract surgery contributes to better visual outcome and may reduce the progression of DR and/or DME after cataract surgery [65] (Figure 7).…”
Section: Progression Of Diabetic Retinopathy After Cataract Surgerymentioning
confidence: 99%
“…In addition, a high level of glycosylated hemoglobin (HbA1c) may indicate progression of changes in the eye fundus [12]. Other factors that may contribute to development of retinopathy are: higher systolic or diastolic blood pressure, hypertension [13], obesity [14], hyperlipidemia [15,16], anemia [17], pregnancy [18], puberty [19], cataract surgery [20], nephropathy [21]. The waist-to-hip ratio (WHR), an indicator of central obesity, has been found to be associated with insulin resistance and serves as an independent risk factor for retinopathy in diabetic patients.…”
Section: Factors That Increase Development Of Diabetic Retinopathymentioning
confidence: 99%
“…In addition, a high level of glycosylated hemoglobin (HbA1c) may indicate the progression of changes in the eye fundus [ 12 ]. Other factors, which may contribute to the development of retinopathy, are higher systolic or diastolic blood pressure, hypertension [ 13 ], obesity [ 14 ], hyperlipidemia [ 15 , 16 ], anemia [ 17 ], pregnancy [ 18 ], puberty [ 19 ], cataract surgery [ 20 ], nephropathy [ 21 ]. The waist-to-hip ratio (WHR), an indicator of central obesity, has been found to be associated with insulin resistance and serves as an independent risk factor for retinopathy in diabetic patients.…”
Section: Introductionmentioning
confidence: 99%